Revision of Dendrochilus (Coleoptera, Scolytinae)—with description of two new species from Tanzania - Jordal, Bjarte H. (Zootaxa, 2021)
The genus Dendrochilus Schedl, 1963 is revised. Two new species are described from the Udzungwa Mountains in Tanzania. Dendrochilus tener sp. nov., and D. udzungwae sp. nov. are closely related with few morphological differences but are clearly separated by molecular data from four gene fragments. Together with the type species D. strombosiopsis Schedl, 1957 from Congo, the genus now includes three species. An identification key to species is provided.